History of Prices V, VI (Quarterly Journal of Economics, 1887)
Journal Article History of Prices V, VI Get access The Quarterly Journal of Economics, Volume 1, Issue 2, January 1887, Page 223, https://doi.org/10.1093/qje/1.2.223-b Published: 01 January 1887